Analisis Gaya Kepemimpinan Walikota Surakarta FX Hadi Rudyatmo - Utari Nourma Diyah; Rina Martini; Nunik Retno Herawati (Journal of Politic and Government Studies, 2015)
ABSTRACTThis study analysed the leadership style of the mayor of Surakarta, namely FX Hadi Rudyatmo. FX Hadi sworn in as mayor of Surakarta on October 19, 2012 by Central Java Governor Bibit Waluyo, replace leadership of Joko Widodo who ran for governor of Jakarta. For the layman who does not know Rudy, most think the mayor Rudy is a private firm, rigid, and difficult to approach. However, it turns behind the grim stature, he is a person who is consulted by their employees. Many people are worried after Jokowi left, Surakarta city development will decrease. But the fact is the mayor Rudy able to maintain or even advance the achievement of Surakarta. There are various style of leadership, including leadership style democratic, authoritarian leadership style and free leadership style. Of several style of leadership, approaching which leadership style FX Hadi Rudyatmo in leading Surakarta?In this study, researchers used a qualitative approach that will present the descriptive data. The research was conducted in the city of Surakarta. the data in this study were obtained through interviews with goverment officials from Section Surakarta City Organization and Personel, Assistant Goverment and the Department of Health, as well as data such as document.FX Hadi Rudyatmo using a democratic leadership style that looks to put the employees who work him as the first and most important factor in running the organization’s activities. In fulfilling the role of control and social relationships, he showed participativeleadership, and in his attempt to apply the theory of human supervision where supervision was fixed according to the rules but still reasonable.